Wheat stress responses during Russian wheat aphid and Bird Cherry Oat aphid infestation: an analysis of differential protein regulation during plant biotic stress responses - Louw, Cassandra Alexandrovna (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
Plants possess a complex and poorly understood network of defence mechanisms that enable them to counteract the effects of abiotic and biotic stress. Aphid phloem feeding is source of biotic stress in plants. Russian wheat aphid and Bird Cherry-Oat aphid feeding cause significant losses in the annual wheat crop, and control by conventional methods such as pesticide application, has proved to be ineffective. Infestation by the Russian wheat aphid has a particularly devastating effect in South Africa. Aphid-resistant wheat cultivars have been identified but an incomplete understanding of the mechanism of the plant's resistance thwarts the development of improved cultivars. A two-dimensional gel electrophoresis method was developed, partially optimised and validated in order to determine the effect of Russian wheat aphid and Bird Cherry-Oat aphid phloem feeding on the Betta and Betta DN wheat proteome. Differentially expressed proteins that were up or down regulated more than two fold were identified using PDQuestâ„¢ Basic software and matched to known wheat proteins stored in the SwissProt protein database on the basis of their molecular mass and isolectric point. Initial analysis of the differential protein expression of Betta and Betta DN wheat in response to Russian wheat aphid and Bird Cherry-Oat aphid phloem feeding at different growth stages revealed that younger plants display higher levels of resistance than older plants. Feeding by the Bird-Cherry Oat aphid does not result in the upregulation of proteins implicated in a defence response, which indicates that the damage incurred by the plant due to feeding by this aphid is not enough to trigger a classic defence response. Feeding by the more damaging Russian wheat aphid resulted in a stress response in susceptible wheat cultivar Betta, and a defence response in resistant wheat cultivar Betta DN. The infestation of Betta DN resulted in the upregulation of putative thaumatins and amylase trypsin inhibitors, indicating that the Betta DN resistance response could be due to the combined effect of protease inhibitors that discourage aphid phloem feeding and the activation of the salicylic acid and jasmonic acid plant defence pathways.
Keywords: Russian wheat aphid; Plants, Effect of stress on; Wheat -- Diseases and pests; Rhopalosiphum; Plant proteins